Working with children affected by large-scale traumatic events - Ajduković, Dean (2005)
The circumstances surrounding families and children who have been living in extremely volatile social environments, that have been exposed to a series of major traumatic events, such as community violence, witnessing death, displacement, and war are presented. First, psychosocial context in which such experiences should be considered are explored. Next, the psychological consequences of such events for children and families are discussed. Experiences in identifying psychological and behavioral reactions among children are described. The empowerment model and the pyramid of community-oriented psychosocial assistance is used to present the framework for alternatives for strengthening individual coping resources of children, as well as family and community support mechanisms. Care-providers’ responses to working with refugees are also addressed. Experiences from a community-based psychosocial interventions are used as an illustrative example from a society affected by war and post-war social divisions. Professional ethical dilemmas, issues around disbalance between the needs and resources, hidden political and professional agendas that affect service delivery for children and social reconstruction of communities recovering from organized violence are also addressed.